The effect comparison of ILM flap and traditional ILM peeling in iMH - Chen, Yiqi; Xu, Yijun; Ye, Xin; Yu, Jiafeng; Wang, Chenxi; Zhang, Zhengxi; Mao, Jianbo; Shen, Lijun (Frontiers in Medicine, 2023)
Purpose: To compare the differences of anatomical structure and visual function between the internal limiting membrane (ILM) peeling and the inverted ILM flap for idiopathic macular hole (iMH), and to evaluate the necessity of the inverted ILM flap for iMH. Methods: A total of 49 iMH patients (49 eyes) were included in this study and followed up for 1 year (12-month), using the inverted ILM flap and ILM peeling respectively. The main foveal microstructures included: the preoperative minimum diameter (MD) and the intraoperative residual fragments (RF), the postoperative ELM reconstruction. Visual function was assessed by BCVA. Results: The hole closure rate was 100% in 49 patients, 15 patients underwent the inverted ILM flap and 34 patients underwent the ILM peeling. There was no difference in postoperative BCVA and ELM reconstruction between the Flap group and the Peeling group with different MD. In Flap group, the ELM reconstruction was closely related to the preoperative MD, the presence of ILM flap and the hyperreflective change of the inner retina at 1-month postoperatively. In Peeling group, the ELM reconstruction was closely related to the preoperative MD, the intraoperative RF at the hole edge (RFHE) and the hyperreflective change of the inner retina. Conclusion: The inverted ILM flap and the ILM Peeling were both able to obtain high closure rate. However, for iMH patients, the inverted ILM flap had no obvious advantages in anatomical morphology and visual function compared with the ILM Peeling.